CoronAsur: religion and COVID-19 (Asia Research Institute, National University of Singapore, 2021)
"Grounded in Asia, with a global and comparative outlook, CoronAsur: Religion and COVID-19 curates reflections, analysis, opinions, commentary pieces, photographic essays and multimedia contributions written by scholars and practitioners at the interface of the COVID-19 pandemic, religious communities and their ritual practices."